À propos de la datation des marques du groupe de Clarianus sur les terres cuites architecturales antiques - Jean-Claude Béal (Gallia)
Roman bricks stamped with the names Clarianus and Nebrigiac were used in the construction of the Gier aqueduct and potentially offer a clue to its date.Roman bricks bearing the Clarianus stamp have been known since the Renaissance and their dating has been a matter of discussion since 1900. Various types of stamps are grouped under the general term “Clarianus”, among them Clarianus Auli Deci Alpini, Clarianus and Clariana. Four Roman “Clarianus” brick stamps (three Clarianus and one Clarianus Auli Deci Alpini) were found in the 17th century at Villards-d’Héria (Jura), in a Roman structure identified at the time as “Roman public baths”. A coin from the reign of the Emperor Hadrian was found in the 19th century at the same place. In the 20th century, on the basis of this discovery, an archaeologist called Lucien Lerat deduced that Roman bricks bearing the “Clarianus” stamp dated from the 2nd century AD.Recent discoveries suggest that the 2nd century AD could be accepted as the production date of all the various stamps grouped under the general category “Clarianus”. However, the chronological sequence of these different stamps cannot be determined at this time.